A history of pew renting in the Church of England. By J. C. Bennett. Pp. xvi + 237 incl. 4 tables. Cham: Palgrave Macmillan, 2024. £119.99. 978 3 031 54426 2 - Jacob, William M. (The journal of ecclesiastical history, 2025)
A history of pew renting in the Church of England. By J. C. Bennett. Pp. xvi + 237 incl. 4 tables. Cham: Palgrave Macmillan, 2024. £119.99. 978 3 031 54426 2 - Volume 76 Issue 3